Penerapan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Perkembangan Kognitif Anak Usia 5-6 Tahun - Kartikasari, Ayu; Durrotunnisa, Durrotunnisa; Fitriana, Fitriana; Zuama, Shofiyanti Nur (Jurnal Ilmiah POTENSIA, 2025)
The main problem addressed in this study is children's cognitive development that has not progressed as expected, characterized by weak abilities in verbal expression and question-answering, which stems from limited development of applied learning models and strategies. This study employed a quasi-experimental design with a sample of 22 group B children at PGRI Sila Darma Tambarobone Kindergarten. Data collection techniques included pretests and posttests, observation, and documentation. The results showed that children's cognitive abilities developed as expected, as reflected in comparisons of average cognitive ability scores before and after color mixing experiment treatments across three aspects: naming colors, observing color mixing processes, and distinguishing between basic colors and mixed color results. Before treatment, the percentage of children in the BSB (Very Well Developed) category was 6.06%, BSH (Developing as Expected) 36.37%, MB (Starting to Develop) 34.85%, and BB (Not Developing) 22.72%. After treatment, the percentage of children in the BSB category increased to 25%, BSH to 38%, MB to 30%, and BB decreased to 7%. These findings demonstrate that implementing a cooperative learning model with group color mixing experiments can enhance children's cognitive development. This study provides evidence of the positive impact of cooperative learning models on children's cognitive development.